Examination of pulmonary embolism in patients in a university hospital (Annals of Medical Research, 2021)
Aim: Pulmonary embolism (PE) is responsible for 5-15% of hospital deaths. The rate of mortality from PE in untreated cases is about 25-30%, while this rate drops down to 2-8% in treated cases. In this study, we aimed to investigate general features of the patients hospitalized in our center due to PE and the factors affecting prognosis. Material and Methods: Patients hospitalized due to PE in Harran University Medical Faculty Hospital between January 2015 and December 2017. Patients’ demographic data, comorbidities, hemogram outcomes at the time of admission, liver function tests, renal function tests, electrolytes and cardiac markers, status of the patients during follow-up (referral to intensive care unit, exitus, ward follow-up) and PE clinical picture (massive, submassive, nonmassive) were recorded. All patients requiring hospitalization due to PE were included in the study, while patients with chronic thromboembolic pulmonary disease, those requiring recurrent hospitalization and patients discharged on own demand were excluded from the study.Results: The study included 40 (38.8%) male and 63 (61.2%) female patients with a mean age of 66±18.1 years. The mean duration of hospitalization was found as 11 days. Of the patients included in this study, 7.7% (n=8) were diagnosed with massive, 10.6% (n=11) with submassive, and 81.5% (n=84) with non-massive PE. Four patients (3.8%) were accepted as in-hospital exitus, 30 (29.1%) patients were transferred to the intensive care unit and 69 (66.9%) patients were followed-up in the thoracic diseases service. When patients diagnosed with non-massive PE were compared with those diagnosed with submassive and massive PE; the levels of magnesium (p=0.003), and troponin (p=0.000) were statistically significantly higher in the group diagnosed with submassive and massive PE. When the groups with and without the need for intensive care were compared, platelet counts were statistically lower in the group which required intensive care (p=0.038).Conclusion: More often hospitalization is needed in female patients due to PE. Although routine laboratory tests give a partial information about the prognosis of PE, cardiac markers are the most commonly used in clinical practice.
Keywords: Hospitalization; laboratory; pulmonary embolism; intensive care